Innovation and Export - Enjolras, Manon (Wiley-Blackwell, 2021)
The concepts of innovation and export are traditionally considered in isolation, both within companies and within the support organizations dedicated to them. As a result, within this broad research field, very little academic work has focused on how to implement their relationship at an operational level. This book proposes a joint diagnostic tool for SMEs, highlighting good practices to be mastered in order to simultaneously improve innovation and export performance, in the form of a virtuous circle. Innovation and Export focuses on the integration of innovation and export into the strategic management of SMEs, for which the use of synergies is a powerful lever to overcome any difficulties in mobilizing significant resources.